A Systematic Review of Scientific Inquiry Research: Trends in Science Literacy and Critical Thinking (2016–2025) - Annisa Mujriati; Agus Abhi Purwoko; Lalu Rudyat Telly Savalas (Balai Publikasi Indonesia, 2025)
The Scientific Inquiry approach has become a central focus of research aimed at enhancing students’ science literacy and critical thinking skills. This article seeks to examine research trends on this topic over the period 2016–2025 through a systematic review and bibliometric analysis. A total of 1,000 documents indexed in Google Scholar were analyzed using VOSviewer software to map conceptual relationships and keyword networks. The findings reveal that the Scientific Inquiry model makes a significant contribution to the development of science literacy and critical thinking through key scientific exploration processes, including observation, hypothesis formulation, data analysis, and evidence-based reasoning. The analysis of publication trends indicates a marked increase in research activity, with journal articles serving as the primary medium of dissemination. The bibliometric analysis identifies research clusters connected to innovative approaches such as ethnoscience, technology-enhanced learning, contextual e-modules, and the integration of 21st-century competencies. The study further underscores the importance of incorporating local contexts and digital technologies to enhance the relevance and effectiveness of science learning. This review offers strategic recommendations to inform future research directions and to promote more innovative, reflective, and contextually grounded science education practices